Listening Skills Strategies (P.I.S.A) Used In Muet: A Preliminary Study - Shahirah Sulaiman; Mohammed Akhiruddin Ibrahim; Azizah Abdul Majid; Nur Safura Ab. Ghaffar; Raimizar Rahim (AESS Publications, 2024)
Non-Indexed Publication